Hey Akini.
For this problem, we know that an inverse map satisfies f(f^(-1)(x)) = x. So as an example you know f(0) = 0 which means f^(-1)(f(0)) = f^(-1)(0) = 0. Can you use this hint to get the rest of the inverse map?
Hey Akini.
For this problem, we know that an inverse map satisfies f(f^(-1)(x)) = x. So as an example you know f(0) = 0 which means f^(-1)(f(0)) = f^(-1)(0) = 0. Can you use this hint to get the rest of the inverse map?
Another example is f(x) = x^2 for x >= 0. y = x^2. To get an inverse function, you switch x's and y's and solve for the new y.
So we get x = y^2 => y = +SQRT(x) so f^(-1)(x) = SQRT(x) and we double check that f^(-1)(f(x)) = SQRT(x^2) = x which is >= 0 as expected.